ANALYSIS OF GOOD CORPORATE GOVERNANCE, DEBT COSTS, AND INVENTORY INTENSITY AGAINST TAX MANAGEMENT - Ester Hanna Gunawan; Faza Wahyu Anggrainy; Sultan Maulana Hakim (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of good corporate governance, debt costs, and inventory intensity on tax management in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The method used is a quantitative method with secondary data from the financial statements of consumer non-cyclicals sector companies listed on the IDX in the period. The sample selection method used was the purposive sampling method by producing 27 companies for five years with a total of 135 observations. Data were analyzed using E-Views software 13. The results of the study show that: (1) Good corporate governance, debt costs, and inventory intensity simultaneously have a significant effect on tax management; (2) Good corporate governance does not have a significant effect on tax management; (3) Debt costs do not have a significant effect on tax management; (4) Inventory intensity has a positive and significant effect on tax management.